(3GdeegO GdcHjQ GdLGeY deYGfi GdSff hGdCMcGe heG JVefg ehWC eGdc ef Gdabg hGdBKGQs - (3YeQ Hf Ydj Hf jhSa GdYKeGfj GdQjaj, GHf GdRgQGA GdhQjGZdj,J (B710 (3g` s
(3ChdgG (B:s
(3cJGH GdQMe HGH eG LGA ai GdQMe s
(3BNQgG (B:s
(3hcGf JRhjL QShd Gddg Udi Gddg Ydjg hSde EjGi hCfG CdYH eY GdLhGQi Je GdSaQ GdMGOi hGdCQHYhf ef cJGH GdeegO (B[ (3GdLGeY GdcHjQ (B] s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B56s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(178 / 40) s
Keywords: (3GdMOjK h GdeUWdMs